The great image: the life story of Vairochana, the translator - Yudra Nyingpo; Jinba Palmo (Shambhala, 2004)
How this precious doctrine occurred in Akanishta -- The appearance of this precious doctrine in the celestial and human realms -- How the effortless vehicle appeared in the three celestial realms -- The appearance of the effortless Ati doctrine in the human realm -- The effortless Ati doctrine flourishing in India -- The appearance of the effortless Ati doctrine in Tibet -- The trials of Vairotsana -- Master Shri Singha entrusts Vairotsana with the entire doctrine -- Vairotsana tames King Rahula Bhibhi's arrogance -- Vairotsana arrives in Tibet -- Vairotsana is banished to Tsawarong -- Vairotsana arrives in Tsawarong and entrusts Yudra Nyingpo with the pith instructions -- Vairotsana goes to the pure lands after completing the instructions in Tibet